Teaching Language in Cross-Disciplinary Contexts - Phuong Nguyen Hoang (Randwick International of Education and Linguistics Science Journal, 2020)
Cross-disciplinarity is more and more important because of the wide specialization demanded by job markets. Separate disciplines are demanded with increasing urgency to integrate their concepts and methods in teaching and research. Only through the intersection of different disciplines can progress and innovation be achieved in specific knowledge areas. It is said that much leading science nowadays progresses not by placing one brick upon the other within a single discipline, but by solving complex problems that cut across many disciplines. Language teaching has to conform to what today’s society demands from professional occupations: a cross-disciplinary role with a result-oriented focus. Cognitive science can provide an adequate model for cross-disciplinary investigation because it integrates linguistic, psychological, philosophical, neurological, computer science, anthropological and historical contributions. Within the cognitive paradigm, a linguistic term does not exclusively exist because of its relations with others but also of culture-based and conventionalized background knowledge. We will use and rely on principles and models of cognitive linguistics to apply and handle language teaching in cross-disciplinary contexts.